Diagnosis and treatment of subchondral bone insufficiency fracture of the knee joint: case series - Gennadiy, Koshman; Ravindrakumar, Eshwar; Jayasooriya Patabadege, Dasun I. A.; Dineshkumar, Prithvi Akaash; Mihasha, Mariyam (International Journal of Research in Orthopaedics, 2024)
Subchondral insufficiency fracture of the knee (SIFK) is a stress fracture that happens under the cartilage usually due to repetitive stress to the bone which is already weakened by non-cancerous diseases which impacts the bone strength and fragility. SIFK is a new nosologic entity that has replaced the diagnosis of spontaneous osteonecrosis of the knee. Primary avascular necrosis of the femoral condyles is a differential diagnosis of subchondral fracture of bone insufficiency of the knee joint, which requires a different approach to treatment. The aim of our study was to evaluate the effectiveness of conservative treatment of subchondral bone insufficiency fracture of the knee joint (SIFK).